Metallogenesis and exploration vectors of the large-scale Tengjia gold deposit, Jiaodong Peninsula (Eastern China): Constraints from monazite U-Pb geochronology and sulfide geochemistry - Jiayao Hao; Liuan Duan; Yu Zhang; Hongtao Zhao; Yongjun Shao; Yuncheng Guo; Xu Wang; Shuling Song (Journal of Asian Earth Sciences, 2026)

Selective recovery of vanadium, molybdenum, and nickel from full-particle spent hydrodesulfurization catalysts via microwave roasting-ammonia leaching - Haoyu Xu; Liang Yu; Zhiyuan Ma; Shuling Fang; Shuai Rao; Dongxing Wang; Lijuan Duan; Hongyang Cao; Zhiqiang Liu (Journal of Environmental Chemical Engineering, 2026)

Photothermal-photodynamic enhanced antibacterial activity of PDA-ALA nanoparticles enables dual-light-responsive sweet cherry preservation - Jianzhuo Du; Tai Gao; Jialin Wang; Pingyu Ge; Haoyang Du; Yu Tong; Jiapei Wu; Weizhuo Xu; Shuling Zhang; Xu Zhao (Food Bioscience, 2026)

Temporal spillovers and habit formation in residential electricity demand response: evidence from large-scale repeated behavioral experiments - Nana Deng; Zhaohua Wang; Shuling Xu (Energy and Buildings, 2026)

Legacy and emerging organophosphate compounds in plateau rivers: Insights into environmental fate and risk from target and nontarget analyses - Zhenfei Han; Jinze He; Yisheng Xu; Wei Zheng; Xuexin Yang; Shuling Duan; Song Tang; Xiaoyu Cui; Yindong Tong; Hongyang Cui (Environmental Research, 2026)

Recent advances in the formation, characterization, and applications of starch-polyphenol complexes: A review - Bo Han; Qianhan Ma; Shuling Yan; Shiyin Jia; Yao Hu; Hao Xu; Siyuan Liu; Hao Zhang; Pengjie Wang; Jiayue Guo (Food Chemistry, 2026)

Apatite geochemistry and Sr isotopes reveal the genesis of Au–W deposits in the Xiangzhong Metallogenic Province, South China: Insights from the Xingfengshan deposit - Lianjie Zhao; Yu Zhang; Han Zheng; Hao Zeng; Hongjie Shen; Shuling Song; Xu Wang (Journal of Asian Earth Sciences, 2026)

Hydraulic fracturing-induced gold remobilization: Pyrite geochemical and sulfur isotopic insights from the Liuan lode gold deposit, South China - Xu Wang; Yu Zhang; Zebin Tang; Yongjun Shao; Bing Xiao; Shuling Song; Xingting Sun; Hongtao Zhao; Lianjie Zhao (Journal of Geochemical Exploration, 2026)

Endoscopic prediction model for detecting advanced rectal polyps after ileorectal anastomosis in familial adenomatous polyposis: a dual-center retrospective study - Zhilin Liu; Xingjie Gao; Shuling Chen; Linfu Zheng; Binbin Xu; Gaozhen Deng; Wen Wang; Kun Lin; Chushu Li; Zhou Ye; Dazhou Li (Familial Cancer, 2026)

Optimizing short-wave infrared (SWIR) indications of alteration minerals for deep mineralization exploration in the Qianchuiliu lode gold deposit, Jiaodong Peninsula - Hongtao Zhao; Liuan Duan; Yu Zhang; Xiaomeng Han; Yongjun Shao; Yuanming Pan; Yuzhou Feng; Xu Wang; Shuling Song; Hongjie Shen (Journal of Geochemical Exploration, 2026)

Quasi-solid-state electrolytes enabling long-life flexible electrochromic energy storage smart windows - Li Liao; Shuling Xiang; Biyou Bao; Guanglong Xu; Chengli Zhang; Qiang Wang; Zhenhu Cao; Wentao Chen; Hongtao Cao; Hongliang Zhang (Chemical Engineering Journal, 2026)

Exogenous melatonin regulates hormone metabolism involved in delaying the ripening process in cherry tomato fruit during storage - Hang Zhang; Yue Wang; Jianhui Cheng; Wenbo Lei; Keyu Xu; Lilai Yin; Chen Huan; Shuling Shen; Lanying Yao; Xiaolin Zheng (Postharvest Biology and Technology, 2025)

Corrigendum to “Dynamic surface restructuring of MoP@Mo-MOF electrocatalysts for efficient alkaline water splitting” [Chem. Eng. J. 521 (2025) 166885] - Xinjuan Liu; Jun Xu; Kun Yang; Dalal A. Alshammari; Mohamed H. Helal; Hang Zhang; Shuai Zhang; Chenchen Zhang; Shuling Shen; Zhihong Tang; Yuhua Xue; Zeinhom M. El-Bahy; et al. (Chemical Engineering Journal, 2025)

Dynamic surface restructuring of MoP@Mo-MOF electrocatalysts for efficient alkaline water splitting - Xinjuan Liu; Jun Xu; Kun Yang; Dalal A. Alshammari; Mohamed H. Helal; Hang Zhang; Shuai Zhang; Chenchen Zhang; Shuling Shen; Zhihong Tang; Yuhua Xue; Zeinhom M. El-Bahy; et al. (Chemical Engineering Journal, 2025)

p-chlorophenylalanine treatment accelerates tomato fruit ripening through hormone synthesis and glycolytic pathway during storage - Keyu Xu; Ran Yan; Hang Zhang; Lilai Yin; Wenbo Lei; Jianhui Cheng; Chen Huan; Yan Liu; Xiaolin Zheng; Shuling Shen (Postharvest Biology and Technology, 2025)

Integration of machine learning and meta-analysis reveals the behaviors and mechanisms of antibiotic adsorption on microplastics - Shuangshuang Bi; Ruoying Wu; Xiang Liu; Peng Wei; Shuling Zhao; Xinru Ma; Enfeng Liu; Hongfeng Chen; Jinling Xu (Journal of Hazardous Materials, 2025)

Decoupling of Au and W mineralization in the Xiangzhong Metallogenic Province (South China): Insights from the Xingfengshan Au–W deposit - Lianjie Zhao; Yu Zhang; Kofi Adomako-Ansah; Matthew J. Brzozowski; Hao Zeng; Chenghua Shi; Yongjun Shao; Hongtao Zhao; Hongjie Shen; Xu Wang; Shuling Song; Xiyue Zheng (Gondwana Research, 2025)

Delayed Detached-Eddy Simulations of Aerodynamic Variability During Carrier-Based Aircraft Landing with a Domain Precursor Inflow Method - Jiawei Fu; Ruifan Hu; Hong Wang; Ke Xu; Shuling Tian (Journal of Marine Science and Engineering, 2025)
Flight tests and wind tunnel experiments face difficulties in investigating the impact of aircraft carrier air-wake on the landing process. Meanwhile, numerical methods generally exhibit low overall computational efficiency in solving such problems. To address the computational challenges posed by the disparate spatiotemporal scales of the ship air-wake and aircraft motion, a domain precursor inflow method is developed to efficiently generate unsteady inflow boundary conditions from precomputed full-domain air-wake simulations. This study investigates the aerodynamic variability of carrier-based aircraft during landing through the turbulent air-wake generated by an aircraft carrier, employing a hybrid RANS-LES methodology on dynamic unstructured overset grids. The numerical framework integrates a delayed detached-eddy simulation (DDES) model with a parallel dynamic overset grid approach, enabling high-fidelity simulations of coupled aircraft carrier interactions. Validation confirms the accuracy of the precursor inflow method in reproducing air-wake characteristics and aerodynamic loads compared to full-domain simulations. Parametric analyses of 15 distinct landing trajectories reveal significant aerodynamic variability, particularly within 250 m of the carrier, where interactions with island-generated vortices induce fluctuations in lift (up to 25%), drag (18%), and pitching moments (30%). Ground effects near the deck further amplify load variations, while lateral deviations in landing paths generate asymmetric forces and moments. The proposed methodology demonstrates computational efficiency for multi-scenario analysis, providing critical insights into aerodynamic uncertainties during carrier operations.

Spatio-temporal variations and influencing factors analysis of coastal wetlands in Tianjin, China - Shuling Yu; Maihemutijiang Mijiti; Min Song; Jingxuan Xu; Dongfang Yuan; Wei Xu (Regional Studies in Marine Science, 2024)

Biochar enhances Cd mineralization through microbially induced carbonate precipitation as a soil remediation strategy for rice paddies - Dinghua Peng; Xianghan Chen; Shuling Zhang; Guoquan Zeng; Chaoqun Yan; Huanyan Luo; Huakang Liu; Heng Xu (Chemosphere, 2024)

The virulence plasmid associated with AHPND in shrimp appears to have originated from Vibrio owensii through a process of homologous recombination of parental plasmids and the transposable insertion of two large fragments - Yesheng Yan; Haojie Lu; Xiaosha Liang; Tianqi Xu; Shuling Yan; Yongxin Yu; Yongjie Wang (Journal of Invertebrate Pathology, 2024)

High-throughput relative quantification of fatty acids by 12-plex isobaric labeling and microchip capillary electrophoresis - Mass spectrometry - Zicong Wang; Miyang Li; Shuling Xu; Liang Sun; Lingjun Li (Analytica Chimica Acta, 2024)

Manufacturing maritime firms’ environmental behaviors: theory and practice - Shuling Mao; Yinxiao Xu (Frontiers in Marine Science, 2024)
Analyzing the factors that influence maritime manufacturing firms’ environmental behavior is of significant theoretical and practical importance, particularly from a managerial cognition perspective. This study applies the regulatory focus theory to examine the complex relationship between environmental quality, regulation, and firms’ environmental actions. Our findings reveal a U-shaped relationship between regional environmental quality and local firms’ environmental consciousness. In regions with either better or poorer environmental conditions, firms demonstrate higher environmental consciousness. Specifically, firms in regions with better environmental quality exhibit a “promotion focus” on environmental issues, leading to proactive engagement in green innovation. Conversely, firms in regions with poor environmental quality adopt a “prevention focus” by pursuing ISO 14001 certification to maintain legitimacy and mitigate penalties. Moreover, we find that incentive regulations are more effective at stimulating green innovation among firms operating in regions with good environmental quality. In contrast, mandatory regulations drive higher ISO 14001 certification rates among firms located in areas with poor environmental quality. This study offers insights into the internal and external motivators of firms’ environmental behavior, contributing to the literature on corporate environmental responsibility. Additionally, it provides policy recommendations to encourage active participation in environmental initiatives among maritime manufacturing firms.

Clean energy consumption in newly poverty-relieved villages: Limited adaptability to external shocks - Bo Wang; Shuling Xu; Nana Deng; Han Shi (Environmental Impact Assessment Review, 2024)

Research on carbon emission measurement and low-carbon path of regional industry - Xue Wu; Shuling Zhou; Guowei Xu; Conghu liu; Yingyan Zhang (Environmental Science and Pollution Research, 2022)

Permeability Anisotropy in High Dip Angle Coal Seam: A Case Study of Southern Junggar Basin - Taiyuan Zhang; Shu Tao; Dazhen Tang; Shuling Tang; Hao Xu; Aobo Zhang; Yifan Pu; Yingying Liu; Qiang Yang (Natural Resources Research, 2021)

Role of mTOR complex in IGF-1 induced neural differentiation of DPSCs - Dan Huang; Shuling Shen; Ming Cai; Lin Jin; Jun Lu; Ke Xu; Jinlong Zhang; Guijuan Feng; Yingzi Hu; Ke Zheng; Xingmei Feng (Journal of Molecular Histology, 2019)

Ecological Offsetting in China’s Coastal Wetlands: Existing Challenges and Strategies for Future Improvement - Shuling Yu; Baoshan Cui; Chengjie Xie; Xu Ma; Ying Man; Zhonghua Ning (Chinese Geographical Science, 2019)

SIRT1 was involved in TNF-α-promoted osteogenic differentiation of human DPSCs through Wnt/β-catenin signal - Guijuan Feng; Ke Zheng; Donghui Song; Ke Xu; Dan Huang; Ye Zhang; Peipei Cao; Shuling Shen; Jinlong Zhang; Xingmei Feng; Dongmei Zhang (In Vitro Cellular & Developmental Biology - Animal, 2016)

Construction of an Off-On Fluorescence System Based on Carbon Dots for Trace Pyrophosphate Sensing - Qiaoli Yue; Yining Hou; Shuzhen Yue; Kaimin Du; Tongfei Shen; Lei Wang; Shuling Xu; Haibo Li; Jifeng Liu (Journal of Fluorescence, 2015)

QSAR studies of antituberculosis drug using three-dimensional structure descriptors - Jianbo Tong; Yang Chen; Shuling Liu; Xiameng Xu (Medicinal Chemistry Research, 2013)

Patterns of variation of the major histocompatibility complex class IIB loci in Chinese goose (Anser Cygnoides) - Xu Zhou; Chunjin Li; Kangle Yi; Hongyan Liang; Lu Chen; Yanling Sun; Shuling Niu; Wei Wu (Immunogenetics, 2009)